Respuesta :

Answer:

[tex]-\frac{8}{9}[/tex]

Step-by-step explanation:

[tex]\dfrac{4}{9}-\dfrac{4}{3}\\\\\mathrm{Least\:Common\:Multiplier\:of\:}9,\:3:\quad 9\\\\\mathrm{Adjust\:Fractions\:based\:on\:the\:LCM}\\\\\frac{4}{3}=\frac{4\times\:3}{3\times\:3}=\frac{12}{9}\\\\=\frac{4}{9}-\frac{12}{9}\\\\\mathrm{Since\:the\:denominators\:are\:equal,\:combine\:the\:fractions}:\\\\\quad \frac{a}{c}\pm \frac{b}{c}=\frac{a\pm \:b}{c}\\\\=\frac{4-12}{9}\\\\=\frac{-8}{9}\\\\=-\frac{8}{9}[/tex]

Answer:

what?

Step-by-step explanation: